Análise comparativa da amplitude do pulso ocular e pressão de perfusão ocular em glaucomatosos, hipertensos oculares e indivíduos normais - Bruno Pimentel de Figueiredo (2012)
Objectives: To correlate ocular perfusion pressure and ocular pulse amplitude in three different groups: Glaucoma patients, ocular hypertensives, and normal individuals. As well as assess the relation between blood pressure parameters with intraocular pressure. Material and Methods: Ninety patients were enrolled for the study. Among them: 30 were recently diagnosed with glaucoma, with no previous history of ocular hypotensive medications; 30 presented ocular hypertension (OH) and no specific signs of glaucoma, either by optic nerve examination or visual field; and 30 volunteers with intraocular pressure (IOP) within normal values (< 21 mmHg) and no evidence of glaucoma. IOP was measured by two different methods, Goldmann applanation tonometry (GAT) anddynamic contour tonometry (DCT). Arterial blood pressure (BP) was taken, automated visual field (VF) and gonioscopy a complete ophthalmic exam was also performed. Central corneal thickness (CCT) was measured by ultrasound pachymetry. Ocular perfusion pressure (OPP) was calculated by the difference between mean arterial pressure (MAP) and IOP. Ocular pulse amplitude (OPA) was directly given by DCT. Results: Mean IOP measured by TAG was 19.0 ± 5.1 mmHg in glaucoma, 22.4 ± 2.1 mmHg in OH, and 12.9 ± 2.2 mmHg in the normals. Mean DCT IOP was 22.7 ± 4.3 mmHg in glaucoma, 22.3 ± 2.8 mmHg in the OH, and 14.3 ± 1.6 mmHg in the normal participants. Mean OPP in the glaucoma group was 46.3 ±7.9 mmHg, in the OH was 41.5 ± 5.2 mmHg, and inthe normals 50.2 ± 7.0 mmHg. Mean OPA was 3.4 ± 1.2 mmHg in glaucoma, 3.5 ± 1.2 mmHg in OH, and 2.9 ± 0.9 mmHg in the normals. Analyzing the three groups together, mean OPA was 3.2 ± 1.2 mmHg. Pachymetry revealed a mean CCT of 529.1 ± 41.4 m, 569.1 ± 30.0 m, and 553.6 ± 28.6 m, in the glaucoma group, OH, and normals, respectively. Mean systolic blood pressure (SBP) for all patientswas 125.8 ± 14.3 mmHg and in the glaucoma, OH, and normal groups, was 131.1 ± 16.7 mmHg, 125 ± 12.3 mmHg, and 121.5 ± 12.1 mmHg, respectively. Mean diastolic blood pressure (DBP) was 82.2 ± 11.3 mmHg, 81.2 ± 6.9 mmHg, and 81.5 ± 9.1 mmHg in the glaucoma, OH, and normal groups, respectively and including all three groups it was 81.6 ± 9.1. Arterial pulse pressure (PP), which is the notation of SBP minus DBP, had mean values of 44.2 ± 10.7 mmHg for all patients, and 48.8 ± 10.5 mmHg, 43.8 ± 11.1 mmHg, and 40.0 ± 8.7 mmHg in theglaucoma, OH, and normal groups, respectively. No correlation between OPA and OPP was found neither in glaucoma (P/r = 0.865/-0.032), OH (P/r = 0.403/-0.156), or normals (P/r = 0.082/-0.307). IOP measured by TAG appeared strongly correlated to DCT (P/r = <0.001/0.858). OPA was correlated with TAG (P/r = <0.001/0.403) and DCT (P/r = <0.001/0.399), showing that OPA closely linked to IOP. A moderate correlation was observed between OPA and PP (P/r = 0.017/0.245) when all groups were analyzed together. The analysis for each group separately, only OH showed a positive correlation between OPA and PP (P/r = 0.005/0.496). Conclusions: No correlation was observed between OPP and OPAanalyzing glaucoma patients, OH, and normal individuals. GAT values were strongly correlated to DCT values, although GAT tended to be lower than DCT, especially in individuals with low CCT. OPA showed only a moderate correlation with PP, drawing the attention to vascular mechanisms regulating ocular perfusion.